Peran Guru Menumbuhkan Kerjasama dan Motivasi Belajar Siswa pada Kelas V Sekolah Dasar - Wulandari, Oky; Sumarno, Sumarno; Dwijayanti, Ida (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2024)
This study was conducted to determine the role of teachers in fostering student cooperation and student learning motivation in learning in the Merdeka Curriculum. This research uses descriptive research with a qualitative approach. The data used is qualitative data. The subject of this research is the fifth-grade teacher of SDN Jomblang 01. The procedure carried out in this research starts from the description, reduction and selection stages. Data collection techniques and instruments are interviews, observation, and documentation. Data analysis used is reduction, data display, conclusion, drawing/verfication. Based on the results of the study, it is found that the role of teachers in fostering student cooperation and student learning motivation is as expected. Learning is carried out in line with the applicable curriculum. In learning in the Merdeka Curriculum, the attitudes developed are the attitude of being actively involved in group work, respecting their friends‘opinions, being able to do cooperation tasks on time, the desire to get maximum learning scores, students’ enthusiasm in doing assignments, and a sense of pleasure when learning takes place.